The role of music performed during Komba girl initiation ceremony of the Lemba people of Zimbabwe. - Runoza, Bengesa (Midlands State University, 2017)
This research is a qualitative ethnographic study with thick description of events. It was done in Mataruse village in Mberengwa. Its focus was on the role of music performed during komba girl initiation of the Lemba. The study used interviews and observation guide to collect the much needed data in the compilation of this research. Information gathered using the above mentioned data collection tools helped in the success of this research. The data was presented and thematically analyzed in a qualitative way. In this research the role of music used during komba ceremony was discussed and explained. It was established that music is the most important cultural element which the Lemba use in all their ritualistic performances and even during komba ceremony.